Rural Nomadic Fulbe Boys’ Primary Schooling: Assessing repertoires of practice in Nigeria - Usman, Lantana (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2007)
ABSTRACT. In recent years, educational policies for boys have not been given as much attention as those for girls in most countries in Sub-Saharan Africa. Rural Nigerian nomadic boys are especially disadvantaged, considering their livelihood is based on a pastoral economy that demands constant migration to interior grasslands in search of pasture. For a more inclusive approach, the federal government of Nigeria promulgated and implemented the Nomadic Educational Policy (NEP). Despite these accommodations, existing school practices affect the boys’ access, attendance, and completion of primary schools. The article elucidates how and why Fulbe nomadic boys are still “left behind᾿ at the primary education level despite specific educational policy developments. This discussion is based on analyzed data and past qualitative study with the boys, and re-situates the nomadic boys’ schooling experiences within some selected learning theories (Bandura, 1977; Maslow, 1971) and discussions of boys’ learning (Epstein, 1998; Gilbert & Gilbert, 1998). The paper concludes with suggestions for policy makers, teachers, and parents to minimize the challenges affecting boys in primary schools. ÉDUCATION PRIMAIRE DES GARÇONS DU PEUPLE FULBE, NOMADES ET RURAUD : ESTIMATION DES RÉPERTOIRES DE PRATIQUE AU NIGERIA RÉSUMÉ. Ces dernières années, les politiques d’éducation des garçons ne font pas l’objet d’autant d’attention que celles touchant les filles en Afrique subsaharienne. Les garçons nomades du Nigeria sont particulièrement désavantagés étant donné que leur mode de vie est fondé sur une économie pastorale qui exige une migration constante vers les terres des prairies de l’intérieur, à la recherche de pâturage. Pour mettre en place un système plus inclusif, le gouvernement fédéral du Nigeria a adopté une politique d’éducation des peuples nomades. Malgré ces efforts, les pratiques des écoles ont une incidence négative sur l’accès des garçons à la scolarisation, sur leur présence en classe et sur leur achèvement du cours primaire. L’auteur explique pourquoi et comment les garçons du peuple nomade Fulbe ne reçoivent pas une éducation primaire convenable malgré les politiques qui ont été mises en place à cette fin. Le débat se fonde sur les données analysées et sur d’anciennes études qualitatives. Il replace l’éducation des garçons nomades dans le contexte de certaines théories de l’apprentissage (Bandura, 1977; Maslow, 1971) et de certains propos sur l’apprentissage des garçons (Epstein, 1998; Gilbert et Gilbert, 1998). En conclusion, l’auteur formule des propositions pour les décideurs, les enseignants et les parents afin de réduire les défis que doivent relever les garçons à l’école primaire.